“The Great Rationalist”: Alexey Vvedensky on Kant in the Context of Russian Kantiana - David O. Rozhin (Кантовский сборник, 2024)
In 1904, the last January issue of the newspaper “Moskoskiye vedomosti” carried an article by Alexey I. Vvedensky, philosopher and theologian, Professor of the Moscow Theological Academy, entitled “The Great Rationalist. On the Centenary of Kant’s Death”. Although the publication could hardly be called unique for its time, as many Russian philosophers and journalists commented on this date, the article merits attention because of the way it represents Kant, and the fact that it sheds light on Vvedensky’s attitudes toward Kantian philosophy. Alexey Vvedensky is to this day a little-known figure in the history of Russian philosophy, such that I thought it would be helpful to preface the publication with a review of the landmarks in the Russian philosopher’s intellectual biography. I go on to demonstrate the ambivalent character of Vvedensky’s attitudes toward Kant’s philosophy. To this end, I show that the Russian philosopher, on one hand, calls for a “return to the universally acclaimed Kant”, whose genius he unreservedly recognises; and on the other hand, he argues that Kant should not only be studied and profoundly reflected on, but also overcome because his rationalism “has desiccated the thought of the new cultured humanity”.